(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2004)
The Upper Bathonian-Middle Oxfordian succession of the Aragonese branch of the Cordillera Ibérica is one of the most completely developed in Europe and includes localities of international importance for Jurassic bio- and chronostratigraphy. Of particular importance are a potential stratotype for the Upper Bathonian of North West Europe and reference sections for a number of Submediterranean Province Middle Oxfordian biostratigraphic units. The intervening Callovian sequence, albeit locally strongly condensed, also includes faunas of key stratigraphical importance. The sequence of stratigraphically important ammonite faunas for this interval is here reviewed and placed in its European context.